Leadership in Orthopaedic Surgery: A Survey of the Value of Leadership Development for Orthopaedic Surgery Faculty. (27th October 2021) - Clark, Sean C.; Miskimin, Cadence; Mulcahey, Mary K.
Abstract : Introduction: The purpose of this study was to survey current orthopaedic department chairs at ACGME-accredited orthopaedic surgery programs in the United States to determine whether department chairs valued the importance of formal leadership training and, if so, to understand the leadership development opportunities available along with the benefits of these program for their orthopaedic faculty. Methods: An anonymous online, voluntary, self-administered questionnaire containing 27 questions was distributed to current orthopaedic department chairs at ACGME-accredited orthopaedic surgery programs in the United States. Results: Thirty-eight responses were received for a response rate of 27.1%. Twenty-three of 38 (60.5%) department chairs believed leadership training is very important for their orthopaedic faculty. Thirty-six of 38 (94.7%) department chairs did not believe that all their current faculty have strong leadership skills. Twenty-eight of 38 (73.6%) respondents have specific training programs for leadership development at their institution. Discussion: Most department chairs (92.1%) viewed leadership training for their orthopaedic faculty as either important or very important. Seventy-four percent of orthopaedic surgery department chairs surveyed indicated that they had a leadership development program in place, with 59.1% being developed within the past 10 years. Benefits of these programs included improved listening and communication skills and management of staff.